ANALISIS KEBUTUHAN APLIKASI LITERASI SAINS BERBASIS QUR’ANI & SOCIO-SCIENTIFIC ISSUES UNTUK MENINGKATKAN KEMAMPUAN ILMIAH SISWA MTs - Deni Ainur Rokhim; Mohammad Hilfi Azra Dzikrulloh; Maya Oki Septiani (Tatar Pasundan : Jurnal Diklat Keagamaan, 2022)
Based data from OECD, Indonesian students’ scientific literacy in 2018 is subaverage. Therefore, researchers do need analysis for developing the scientific literacy application based on Al-Qur'an and Sosio-Scientific issues. The purpose of this research is to obtain information from teachers and students’ perspective about the characteristics of ideal scientific literacy application. This research uses descriptive qualitative research methods. The research subjects consisted of 10science teachers and 300madrasah students from 4 districts in Malang Regency. Scientific literacy emphasizes the need for a balance between various abilities and requires skills in deciding Sosio-Scientific issues. Integration between science and religion is also highly considered in terms of avoiding free value of science. The results showed that the science literacy application development based on Al-Qur’an Sosio-Scientific issues is needed with certain criteria.Keywords: Al-Qur’an; Scientific Abilities; Scientific Literacy; Sosio-Scientific Issues